(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2024)
Introduction: Tuberculosis (TB) is a serious public health issue in Nepal and globally. The burden of tuberculosis is further worsened by coexisting anxiety and depression. This study aims to assess the prevalence and factors associated with depression and anxiety symptoms among TB patients in Kaki District, Nepal. Methods : A community based cross sectional study was conducted among the TB patients residing in the Kaski district from March to September, 2023. Structured interview and validated questionnaires were used for data collection. Pretesting was done on 10% sample size in similar area to check the adaptability of the questionnaire. Data was entered in Epi-data (version 3.1) and exported to SPSS (version 20) for analysis. Binary logistic regression was used to observe the relationship between dependent and independent variables. Results: A total of 239 TB patients were included in the study. The prevalence of depression and anxiety was found to be 35.1% and 31.8% respectively. Factors such as nuclear family of participants was associated with higher levels of depression. Individuals who belonged to nuclear families and had knowledge of TB symptoms and unfriendly behaviors from the health workers were more prone to induce the experience of anxiety. Family structure exhibited a consistent positive association with both depression and anxiety in bi-variate analysis. Conclusions: The study findings highlight a high prevalence of anxiety and depression among TB patients. It is of utmost importance to underscore the critical significance of urban residency, as well as address the pressing necessity for a transformation in the attitudes of health workers. This shift is vital in ensuring that healthcare delivery effectively meets the diverse needs. Timely counseling for both patients and their families is crucial in mitigating anxiety and depression. It’s essential to provide adequate counseling and impart TB related knowledge to address these mental health challenges effectively.